Концепція забезпечення економічної безпеки бізнес-процесів торговельного підприємства - Коптєва (Фадєєва), Ганна Миколаївна (Видавничий дім "Гельветика", 2020)
У статті проведено аналіз підходів учених до обґрунтування сутності системи економічної безпеки підприємства та механізму її забезпечення. Для обґрунтування системи економічної безпеки підприємства автором запропоновано використання комплексного підходу на основі поєднання системного й процесного підходів до її побудови. За результатами проведених досліджень та власних напрацювань сформульовано функції системи економічної безпеки бізнес-процесів торговельного підприємства. Автором запропоновано визначення понять "забезпечення економічної безпеки бізнес-процесів підприємств торгівлі" та "концепція забезпечення економічної безпеки бізнес-процесів торговельного підприємства". Сформовано концепцію забезпечення економічної безпеки бізнес-процесів торговельного підприємства.

The process of ensuring the economic security of business processes of a trade enterprise, as a determining condition for its sustainable and successful operation, is based on the development of conceptual provisions for ensuring the economic security of the enterprise. The article analyzes the approaches of scientists to the theoretical substantiation of the essence of the system of economic security of the enterprise, the mechanism of its provision. To justify the system of economic security of the enterprise, it is proposed to use an integrated approach based on a combination of system and process approaches to its construction. Based on the results of research and own developments, the functions of the system of economic security of business processes of a trade enterprise are formulated. Consideration of economic security from the position of value-oriented management enables you to define the objects of security management at the enterprise, and structuring business processes, resources, and factors is the basis for the formation of a fundamentally new concept of "economic security of enterprise". Today not sufficiently resolved issues to ensure the economic security of trade enterprise, modeling the development of the concept of economic security of the enterprise on the basis of the analysis of structural relationships of external and internal threats and dangers. In this regard, it is necessary to form a conceptual approach to ensuring the economic security of trade enterprises. The author offers definitions of the concepts "ensuring economic security of business processes of trade enterprises" and "the concept of ensuring economic security of business processes of a trade enterprise". Formed a conceptual model of economic security of business processes of a trade enterprise based on modern management tools including system and process approach, which, in turn, provide an opportunity to clearly structure the main components of the conceptual provisions to ensure sustainable functioning and development of a trade enterprise in the market based on the balance of its functional components in a dynamic environment.
The concept of ensuring economic security of business processes of a trade enterprise
Keywords: економіка; державні органи; конкурентоспроможність; управління; economics; government agencies; competitiveness; management